Verbal and Visual Messages in Advertisements of Men’s Accessories - Adi Prawangsa, Prisma (Humanis; Vol 22 No 1 (2018), 2018)
The title of this paper is “Verbal and Visual Messages in Advertisements of Men’s Accessories”. The discussion in this study is aimed to analyse the verbal and visual messages presented in each advertisements and analysing the meanings and functions of visual and verbal signs in each advertisements. The data of this study were taken from internet with different sources. They are Tudor, Velocity 773, Ray-Ban and Young’s Hats advertisement. The method and technique of collecting data used in this paper was library research and note taking, then the collected data was analysed descriptively by the theory of meaning and function proposed by Leech and theory of verbal and visual message proposed by Ferdinand de Saussure. The results of the analysis show that there are three types of meaning and function that can be identified in this study. Those meanings are connotative, thematic, and conceptual meaning. The functions are aesthetic, expressive and informational function.